(untitled) (Baghdad Science Journal, 2011)
Ortho amino hydrazobenzene (L) has been prepared from the reaction of ortho amino phenyl thiol with phenyl hyrazan in mole ratio(1:1). It has been characterized by elemental analysis (C, H, N), IR, UV–Vis. The complexes of the bivalent ions (Co, Ni, Cu, Zn, Pd, Cd, Hg and Pb) and the trivalent (Cr) have been prepared and characterized too. The structural have been established by elemental analysis(C,H,N), IR , UV – Vis spectra , conductivity measurements , atomic absorption and magnetic susceptibility . The complexes showed characteristic behaviour of octahedral geometry around the metal ion and the( N,N) ligand coordinated in bidentate modeexcept with pd showed square planer. ? ,kf , ?max for the complexes were estimated too . ? for Co – complex was calculated . The study of biological activity of the ligand (L) and its complexes showed various activity toward Streptococcus pyogenes Staphylococcus aureus , Pseudomonas aeruginosa , E. coli and Candida albicans .